Pengukuran Beban Kerja Mental Bagian Marketing PT. Pindo Deli di Masa Covid-19 dengan Metode NASA TLX - Rahdiana, Nana; Hakim, Afif; Sukarman (TALENTA Publisher, 2021)
PT. Pindo Deli is a national company that produces paper, which is located in Kutamekar Village BTB6/9, Karawang Regency, West Java. It produces various types of paper with a market share of 60% for exports and 40% for domestic. The condition of the Covid-19 pandemic also has an impact on the marketing and sales of paper, namely a decrease in the number of requests from the export and domestic markets. This condition certainly has affected the marketing department because it is still determined to be able to sell paper to the market. Job as marketing tend to have a high risk of mental workload, because they are required to always involve the brain's performance in completing their work. The purpose of this study is to measure the level of mental workload in the marketing department at the manager level, namely the regional managers and product managers in meeting their job demands, especially during the Covid-19 pandemic. The method used to measure the mental workload of managers is NASA TLX method. From the research results, it is found that 42% of manager had a high level of mental workload and the remaining 58% were in the very high category.